Analisis Faktor-Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi pada Lembaga Perkreditan Desa - Safitri, Gita Najmi; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 31 No 2 (2021), 2021)
This study aims to determine the effect of user involvement variables in system development, user education and training programs, personal technical skills, user communication and information systems developers and organizational size on the performance of the Accounting Information System. Respondents in this study were 40 employees found in the LPD in South Denpasar District. Determination of the sample using purposive sampling method. The analytical tool used is multiple regression analysis. The results of this study indicate that the variables of user involvement in system development, user training and education programs, personal technical skills, user communication and information system developers and organizational size have a significant positive effect on SIA performance. Keywords: User Involvement; Training and Education; Personal Engineering; User and Developer Communication.